2004
DOI: 10.1093/jb/mvh112
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Heme Regulatory Motif in the Heme-Mediated Inhibition of Mitochondrial Import of 5-Aminolevulinate Synthase

Abstract: 5-Aminolevulinate synthase (ALAS) is a mitochondrial enzyme that catalyzes the first step of the heme biosynthetic pathway. The mitochondrial import, as well as the synthesis, of the nonspecific isoform of ALAS (ALAS1) is regulated by heme through a feedback mechanism. A short amino acid sequence, the heme regulatory motif (HRM), is known to be involved in the regulatory function of heme. To determine the role of the HRM in the heme-regulated transport of the nonspecific and erythroid forms of ALAS in vivo, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 0 publications
4
73
0
1
Order By: Relevance
“…The regulation of ALAS1 expression also occurs at the post-transcriptional level. Namely, the translation of ALAS1 mRNA is inhibited by heme (Munakata et al 2004). The translocation of the ALAS1 precursor into mitochondria is also inhibited by heme.…”
Section: Heme-dependent Regulation Of Hemoprotein Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of ALAS1 expression also occurs at the post-transcriptional level. Namely, the translation of ALAS1 mRNA is inhibited by heme (Munakata et al 2004). The translocation of the ALAS1 precursor into mitochondria is also inhibited by heme.…”
Section: Heme-dependent Regulation Of Hemoprotein Biogenesismentioning
confidence: 99%
“…The enzyme produces heme for a variety of hemoproteins. The level of intracellular uncommitted heme is extremely low since increased levels of free heme are toxic, so heme biosynthesis is tightly regulated at the step of ALAS1 by multiple mechanisms such as (1) preventing the transfer of ALAS1 precursor to the mitochondria, (2) decreasing the stability of ALAS1 mRNA, and (3) repressing the transcription of ALAS1 mRNA in mammals (Munakata et al 2004). On the other hand, the drug-responsive elements that mediate the direct activation of the transcription were identified in the promoter region of the murine, chicken and human ALAS1 genes (Fraser et al 2002;Podvinec et al 2004).…”
Section: Biosynthesis and Regulation Of Heme Metabolism In Mitochondriamentioning
confidence: 99%
“…HRM-mediated heme binding also remains controversial for HO-2 (33). The role of heme in regulating ALAS1 and ALAS2 import into mitochondria is also disputed (36,37). Heme inhibits potassium efflux from BK channels.…”
Section: Non-nr Heme Sensorsmentioning
confidence: 99%
“…However, studies with ALAS-transfected quail fibroblasts showed that rat ALAS2 mitochondrial import was not affected by heme. However, ALAS1 import was inhibited by heme, and studies on Cys-to-Ser mutant CP variants showed that CP motifs in HRM1 and HRM3 are important in this heme-mediated inhibition (37).…”
Section: Heme Homeostasismentioning
confidence: 99%
“…Cys-384 is involved in a redox-regulated ligand switch in which it forms a disulfide bond with Cys-374, which lowers heme affinity (38). HRMs have also been proposed to control the activity or stability of several regulatory proteins including an iron-responsive regulator in bacteria (39), a kinase (eIF2␣ kinase or heme-regulated inhibitor (HRI)) (40), a mammalian transcription repressor (Bach1) (41), 5-aminolevulinate synthase (42), and the yeast transcription factor Hap1, which mediates the effects of oxygen on transcription (43). In 5-aminolevulinate synthase, three HRMs facilitate the heme-dependent inhibition of mitochondrial import of the synthase, while in the mammalian iron-responsive protein IRP2, heme binding to the HRM appears to regulate protein degradation (44).…”
mentioning
confidence: 99%